Emission and migration of PCDD/Fs and major air pollutants from co-processing of sewage sludge in brick kiln. (February 2021) - Ying, Yuxuan; Ma, Yunfeng; Li, Xiaodong; Lin, Xiaoqing
Abstract: The annual output of sewage in China is increasing rapidly and continues to grow, so there is an urgent need for a treatment other than landfills. Among various treatment methods, brick production coprocessing of sewage sludge is technically and economically advantageous. The emission characteristics of typical brick kiln coprocessing of sewage sludge with an annual production of 60 million bricks were studied. The major air pollutants and PCDD/Fs in gas and soil were determined. Particulate matter and SO2 contributed most before treatment, with concentrations of (1.017 ± 0.089) × 10 4 mg/Nm 3 and (2.770 ± 0.251) × 10 3 mg/Nm 3, respectively. After cleaning, the average emitted concentrations of major air pollutants were permissive and homogeneous: 58.13 ± 5.51 mg/Nm 3 for NOx, 30.15 ± 9.12 mg/Nm 3 for HCl, 28.63 ± 14.33 mg/Nm 3 for SO2, 23.76 ± 3.31 mg/Nm 3 for particulate matter, and 356.8 ± 99.1 for odor. The PCDD/Fs in the exhaust gas and ambient air showed similar distributions and fingerprint characteristics. The annual emission amounts of the PCDD/Fs were 0.265 g/year and 0.0393 g TEQ/year. Moreover, correlation analysis indicated that PCDD/Fs were most relevant to HCl, and particulate matter might be important to SO2 and fluoride. Further relativity studies showed that the brick kiln was a source of PCDD/Fs but not a main source of major air pollutants to the surrounding environment. All the above pollutants from the brick kiln were permissive with relevant national standards. The results could help with pollution inventories for the brick and tile industry and sewage sludge disposal process. Graphical abstract: Image 1 Highlights: Emission characteristics of brick kiln co-disposing sludge are first determined. Annual emission amounts of PCDD/Fs are 0.265 g/year and 0.0393 g TEQ/year. HCl is most relevant to PCDD/Fs among major air pollutants. Brick kiln contributes most PCDD/Fs to region but less major air pollutants.